Alteration of gut microbiome in goslings infected with goose astrovirus - Haiqin Li; Qi Su; Duanfeng Fu; Haoyu Huang; Zhihua Lu; Cheng Huang; Yunfeng Chen; Meifang Tan; Jiangnan Huang; Zhaofeng Kang; Qipeng Wei; Xiaoquan Guo (Poultry Science, 2024)
ABSTRACT: Goose astrovirus (GoAstV) is an emerging avian pathogen that induces gout in goslings with a mortality of up to 50%. Organ damage caused by GoAstV infection was considered the cause of gout, but it is still unclear whether other factors are involved. Human and murine studies have linked the gut microbiome-derived urate and gout, thus we hypothesized that gut microbiome may also play an important role in gout induced by GoAstV infection. This study tested the pathogenicity of our isolated GoAstV genotype 2 strain on goslings, while the appearance of clinical signs, histopathological changes, viral distribution and the blood level of cytokines were monitored for 18 d postinfection (dpi). The dynamics in the gut microbiome were profiled by 16S sequencing and then correlated with GoAstV infection. Results showed that this study successfully developed an experimental infection model for studying the pathogenicity of the GoAstV infection which induces typical symptoms of gout. GoAstV infection significantly altered the gut microbiome of goslings with the enrichment of potential proinflammatory bacteria and depletion of beneficial bacteria that can produce short-chain fatty acids. More importantly, the microbial pathway involved in urate production was significantly increased in goslings infected with GoAstV, suggesting that gut microbiome-derived urate may also contribute to the gout symptoms. Overall, this study demonstrated the role of gut microbiome in the pathogenesis of GoAstV infection, highlighting the potential of gut microbiome-based therapeutics against gout symptoms.